Modulation of histamine release from human colon mast cells by protease inhibitors - He, Shao-Heng (World J Gastroenterol, 2004)
AIM: To investigate the ability of protease inhibitors to modulate histamine release from human colon mast cells. METHODS: Enzymatically dispersed cells from human colon were challenged with anti-IgE or calcium ionophore A23187 in the absence or presence of tryptase and chymase inhibitors, and histamine release was determined. RESULTS: IgE dependent histamine release from colon mast cells was inhibited by up to approximately 37%, 26% and 36.8% by chymase inhibitors Z-Ile-Glu-Pro-Phe-CO(2)Me (ZIGPFM), N-Tosyl-L-phenylalanyl-chloromethyl ketone (TPCK), and α(1)-antitrypsin, respectively. Similarly, inhibitors of tryptase leupeptin, N-tosyl-L-lysine chloromethyl ketone (TLCK), lactoferrin and protamine were also able to inhibit anti-IgE induced histamine release by a maximum of some 48%, 37%, 40% and 34%, respectively. Preincubation of these inhibitors with cells for 20 min before challenged with anti-IgE had small effect on the inhibitory actions of these inhibitors on colon mast cells. A specific inhibitor of aminopeptidase amastatin had no effect on anti-IgE induced histamine release. The significant inhibition of calcium ionophore induced histamine release was also observed with the inhibitors of tryptase and chymase examined. Apart from leupeptin and protamine, the inhibitors tested by themselves did not stimulate colon mast cells. CONCLUSION: It was demonstrated that both tryptase and chymase inhibitors could inhibit IgE dependent and calcium ionophore induced histamine release from dispersed colon mast cells in a concentration dependent of manner, which suggest that they are likely to be developed as a novel class of anti-inflammatory drugs to treat chronic of colitis in man.